TRAINING OF FUTURE SPECIALISTS IN PRESCHOOL AND PRIMARY EDUCATION FOR MEDIATION IN PROFESSIONAL ACTIVITIES - SHYSHAK, Andriana; RUDENSKYI, Rostyslav; HOMOTIUK , Oleksandr (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The article presents a study of the problem of training future specialists in preschool and primary education to carry out mediation in professional activities. Its relevance is stipulated by the requirements for educators and primary school teachers contained in the standards of training of applicants for the first (bachelor's) and second (master's) levels of higher education, professional standards and the need to prevent and resolve conflicts between preschoolers, primary schoolchildren, parents and colleagues. The author describes the stages of the mediation process, which include: introduction, outlining the role of the mediator, adoption of ground rules; continuous and complete telling of each party's story and expression of their own feelings; formulation of questions by the parties to each other to discuss the problem in the situation that has arisen; offering by the parties of options for effective solutions; agreement of the participants to one or more solutions, which is certified by a written agreement signed by the parties and the mediator. The author identifies specific tools of mediation involving children of preschool and primary school age: visualization, game and communication tools. Examples of visualization tools for mediation are given: cards that reflect emotions; a colour scale of emotions in the form of a rainbow or a mood flower; creating a story in drawings. Role-playing and theatrical activities are described as game-based mediation tools. It is noted that the communication tools of mediation are the use of the ‘subject of speech’ rule and the ‘I-message’ technique, the creation of a code of peace. It is determined that during the study in higher education institutions, in order to prepare future specialists in preschool and primary education for mediation in professional activities, it is necessary to promote the qualitative mastery of theoretical knowledge in the field of conflict resolution, as well as practice in implementing mediation tools and analysing their strengths and weaknesses.